A first interspecific Oryza sativa x Oryza glaberrima microsatellite-based genetic linkage map - Lorieux, Mathias; Ndjiondjop, M.N.; Ghesquière, A. (2000)
Oryza glaberrima is an endemic African cultivated rice species. To provide a tool for evaluation and utilisation of the potential of O. glaberrima in rice breeding, we developed an interspecific O. glaberrimaxOryza sativa genetic linkage map. It was based on PCR markers, essentially microsatellites and STSs. Segregation of markers was examined in a backcross (O. sativa/O. glaberrima//O. sativa) population. Several traits were measured on the BC1 plants, and major genes and QTSs were mapped for these traits. Several of these genes correspond well to previously identified loci. The overall map length was comparable to those observed in indicaxjaponica crosses, indicating that recombination between the two species occurs without limitation. However, three chromosomes show discrepancies with the indicaxjaponica maps. The colinearity with intraspecific maps was very good, confirming previous cytological observations. A strong segregation-distortion hot spot was observed on chromosome 6 near the waxy gene, indicating the presence of s10, a sporo-gametophytic sterility gene previously indentified by Sano (1990). The main interests of such a PCR-based map for African rice breeding are discussed, including gene and QTL localisation, marker-assisted selection, and the development of interspecific introgression lines.